Merkel cell carcinoma: An algorithm for multidisciplinary management and decision-making. (February 2016) - Prieto, Isabel; de la Fuente, Teresa Pérez; Medina, Susana; Castelo, Beatriz; Sobrino, Beatriz; Fortes, Jose R.; Esteban, David; Cassinello, Fernando; Jover, Raquel; Rodríguez, Nuria
Highlights: We have written a multidisciplinar and updated review of Merkel cell carcinoma. We describe how tumor and node management involve different specialists. We demonstrate that their respective decisions and interventions are interrelated. We propose a multidisciplinary decision algorithm for managing this tumor. We update the current ongoing clinical trials with new drugs for Merkel cell carcinoma. Abstract: Merkel cell carcinoma (MCC) is a rare and aggressive neuroendocrine tumor of the skin. Therapeutic approach is often unclear, and considerable controversy exists regarding MCC pathogenesis and optimal management. Due to its rising incidence and poor prognosis, it is imperative to establish the optimal therapy for both the tumor and the lymph node basin, and for treatment to include sentinel node biopsy. Sentinel node biopsy is currently the most consistent predictor of survival for MCC patients, although there are conflicting views and a lack of awareness regarding node management. Tumor and node management involve different specialists, and their respective decisions and interventions are interrelated. No effective systemic treatment has been made available to date, and therefore patients continue to experience distant failure, often without local failure. This review aims to improve multidisciplinary decision-making by presenting scientific evidence of the contributions of each team member implicated in MCC management. Following this review of previously published research, the authors conclude that multidisciplinary team management is beneficial for care, and propose a multidisciplinary decision algorithm for managing this tumor.